Effect of N and K Fertigation Levels on Yield Attirbutes, Yield and Water Productivity of Coloured Capsicum (Capsicum annuum var. grossum) Hybrids Under Shade Net - S. SRIDEVI, K. SHILPA, M. UMA DEVI, K. AVIL KUMAR and (The Journal of Research, PJTSAU, 2020)
Water and fertilizers are the most importantinputs in agriculture and the efficient use of theseresources is important for maximizing yield. Fertigationenables the application of water soluble fertilizers moreuniformly and efficiently in the crop root zone. It alsohelps in the application of nutrients according to thecrop requirement at different growth stages.